Amoxicillin Adsorptive Hydrogels Based on Quaternary Ammonium Polymer and Carboxylated Cellulose Nanocrystals - Bruna-Bugueno, J; Roa-Ruiz, K; Oyarce-Riveros, E; Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2025)
Antibiotic water contamination is a critical environmental concern driving the development of efficient adsorbents for its removal. This study presents the synthesis and characterization of poly(3-[(acryloylamino)propyl]trimethylammonium) hydrogels with carboxylated cellulose nanocrystals (CCNCs) for the adsorption of amoxicillin. The hydrogels were synthesized by radical polymerization, incorporating 5 % and 10 % CCNCs with different degrees of oxidation. Where, CCNCs have a high surface area and functionalization with carboxyl groups, contributing to improve the structural and adsorbent properties of the material. Thermogravimetric analysis and scanning electron microscopy showed that the incorporation of CCNCs increased the degradation temperature by approximately 10 °C and improved structural integration. Hydration and compression tests indicated that the incorporation of 5 % CCNCs achieves a balance between swelling and toughness. A maximum adsorption capacity of 157.69 mg g−1 was achieved at pH 10, with a removal efficiency of 86 % (with 5 wt% L-CCNCs). The adsorption process followed the Elovich kinetic and Redlich-Peterson isothermal models, suggesting a mechanism driven by electrostatic interactions and hydrogen bonding. The efficiency decreased to 40 % after three regeneration cycles with 1 mol L−1 NaCl. Computational simulations are consistent with the previous experimental study, indicating that the homogeneous dispersion of CCNC improves accessibility to the active sites and increases the flexibility of the hydrogel. In summary, the developed materials offer an effective, reusable, and sustainable alternative for the removal of antibiotics from wastewater. © 2025 Elsevier B.V.
Keywords: Adsorption; Amoxicillin; Cellulose nanocrystals; Emerging contaminants; Molecular dynamics; Quaternary ammonium hydrogels